Exploring the lecturers’ experiences in teaching English in TESOL Classroom - Fhonna, Rahmi (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2024)
In Aceh, English is still taught as foreign language and its teaching practices have experienced a rapid growth in the last decades. This qualitative phenomenological study investigates the complex experiences of TESOL lecturers, examining their perspectives towards this issue, exploring teaching methodologies used, and challenges faced in contemporary language education contexts. Through in-depth semi-structured interviews with five experienced lecturers at English Education Department of UIN Ar-Raniry Aceh, this study explores the multifaceted nature of English language teaching. The study reveals that successful TESOL instruction transcends traditional linguistic pedagogy, requiring sophisticated, adaptive strategies that integrate technological innovations, cultural sensitivity, and personalized learning approaches. Key findings highlight the critical importance of flexible teaching methodologies to empower the students in English communication, technology integration to maintain students’ motivation in English learning, and continuous professional development in addressing the dynamic needs of language learners. The study demonstrates that effective TESOL lecturers navigate complex educational landscapes by continuously adapting their pedagogical practices to meet evolving student needs and global communication challenges.